¿Donde esta el pollo? Cuba, sovranità alimentare e ontologia della scarsezza - Elena Zapponi (Archivio Antropologico Mediterraneo)
Paradigms of sustainability are being formed in Cuba along autonomous paths, marked by the imposition of the bloqueo. The analysis focuses on changes rooted in the long-lasting crisis that followed the 1990s and on an 'ontology of scarcity', a consequence of the pandemic, the exacerbated economic crisis, and the recent reorganisation of the monetary system; a time marked by an increased sense of daily lucha on the part of citizens who experience supply difficulties, urban peregrinations in search of food, and an unprecedented migratory exodus. The reflection focuses on the libreta de abastecimiento, an instrument of rationing basic foodstuffs. It is considered in its production as a habitus but also as a contradictory object, a metaphor for scarcity, a promise of the guarantee of food that is concretely often unavailable. Moreover, a metaphor for the recent changes in Cuban resolver is the chicken, an imported food, a sign par excellence of the problems of disruption of food chains, of the difficulties of distribution and purchase queues that modify the practice of everyday time. The passages outlined analyse the feeling of cognitive dissonance on the part of citizens with respect to state guarantees in the context of the victorious 'bet' of Cuban vaccination policies.